2022
DOI: 10.1186/s12884-022-05231-8
|View full text |Cite
|
Sign up to set email alerts
|

The impact of prolonged landscape fire smoke exposure on women with asthma in Australia

Abstract: Background Little is known about the physical and mental health impact of exposure to landscape fire smoke in women with asthma. This study examined the health impacts and information-seeking behaviours of women with asthma exposed to the 2019/2020 Australian fires, including women who were pregnant. Methods Women with asthma were recruited from the Breathing for Life Trial in Australia. Following the landscape fire exposure period, self-reported d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 41 publications
(59 reference statements)
0
9
0
Order By: Relevance
“…The results related to respiratory and non-respiratory symptoms, asthma symptoms and exacerbation and mental health are reported elsewhere [ 34 ]; briefly, 82% participants experienced respiratory and non-respiratory symptoms and 85% asthma symptoms during the landscape fire period [ 34 ]. Furthermore, 86% reported having an asthma exacerbation during the fire period, with 20% reporting they started/increased OCS use for an asthma exacerbation(s) during the fire period.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The results related to respiratory and non-respiratory symptoms, asthma symptoms and exacerbation and mental health are reported elsewhere [ 34 ]; briefly, 82% participants experienced respiratory and non-respiratory symptoms and 85% asthma symptoms during the landscape fire period [ 34 ]. Furthermore, 86% reported having an asthma exacerbation during the fire period, with 20% reporting they started/increased OCS use for an asthma exacerbation(s) during the fire period.…”
Section: Resultsmentioning
confidence: 99%
“…Participants had a median [Q1, Q3] age of 30 [ 28 , 34 ] years and BMI of 27.6 [25.5, 33.5] kg/m 2 . Most (75%) participants were overweight or obese and 4% were current smokers.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our participants acknowledged the utility of such messaging and their reliance on it in their preparations for possible evacuation. However, their comments suggested that there was a lack of information specific to pregnant women or women with young children and this made it more difficult for them to feel, or be, adequately prepared, particularly in the midst of experiencing a heightened sense of risk [22]. The impact of the fires on both traditional lines of communication and household amenities (relied upon to provide care for newborns) made it difficult for the participants to act with the same level of certainty in decisions about their personal crisis/disaster management preparations.…”
Section: Discussionmentioning
confidence: 99%
“…Exposure to LFS in pregnant women may have a direct impact on asthma, increasing airway inflammation and reducing lung function causing asthma exacerbations, which may increase the risk of adverse pregnancy outcomes including low‐birth weight and preterm birth 22,23 . A study of the health impact of the 2019–20 Australian bushfire period found that pregnant women with asthma were more likely to report respiratory and non‐respiratory symptoms during compared to after this periods 24 . Moreover, pregnant women with asthma also had higher anxiety scores during compared to after the fires 24 .…”
Section: Impact Of Lfsmentioning
confidence: 99%